The role of country-specific factors and the adoption of a global business language - Haapamäki, Elina (Association of Business Schools Finland, 2019)
The global business world requires precise, reliable ﬁnancial information. It has been argued that the International Financial Reporting Standards (IFRSs) and International Standards on Auditing (ISAs) are important tools in developing a global business language. Historically, countries have developed and pursued their own accounting and auditing standards; however, as national markets grow into a global market, a common set of accounting and auditing standards is needed. Consequently, there is a trend towards IFRS and ISA harmonization worldwide. This study aims to investigate why some countries have adopted the IFRS and ISA standards while others have only partially adopted them. Moreover, previous studies have not examined the adoption of IFRS and ISA and country-speciﬁc factors simultaneously. This study suggests that voice and accountability, regulatory quality, and control of corruption achieved within a national economy are all predictive of the degree to which the IFRSs and ISAs are adopted across 113 jurisdictions.
Keywords: IFRS; ISA; global harmonization; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|